African American Stroke Survivors: More Caregiving Time, but Less Caregiving Burden. (February 2017) - Skolarus, Lesli E.; Freedman, Vicki A.; Feng, Chunyang; Burke, James F.
Abstract : Background—: Blacks have higher stroke incidence and experience greater poststroke disability than whites. To optimize care for stroke survivors, it is important to understand the amount of care that they receive and the implications for stroke caregivers. Methods and Results—: Data from 2 nationally representative, population-based studies, the NHATS (National Health and Aging Trends Study) linked to the NSOC (National Study of Caregiving), were used to identify elderly stroke survivors and their caregivers. We compared hours of care received and unmet activity need among the 581 white and 225 black stroke survivors. We then performed racial comparisons of positive and negative aspects of caregiving reported by caregivers of black and white stroke survivors. Black stroke survivors were more likely than white stroke survivors to have a caregiver (62.5% versus 49.7%; P <0.01) and received on average more hours of help per week (31.7 versus 20.5; P <0.01). There was little racial difference in unmet need for assistance. Caregivers of black stroke survivors reported more positive aspects of caregiving than caregivers of white stroke survivors (6.8 versus 6.0; P <0.01). There was no racial difference in negative aspects of caregiving, depression, or anxiety. Conclusions—: Black stroke survivors received an average of ≈11 more hours of care than white stroke survivors without substantial differences in unmet need. Despite providing more hours of care, caregivers of black stroke were more positive about their caregiver role than caregivers of white stroke survivors. Abstract : Supplemental Digital Content is available in the text.